Biology a self-teaching guide - Garber, Steven 1950- (Jossey-Bass, 2020)
"Steven D. Garber explains all the major biological concepts and terms in this newly revised edition, including the origin of life, evolution, cell biology, reproduction, physiology, and botany. The step-by-step, clearly structured format of Biology is fully accessible to students, providing an easily understood, comprehensive treatment of all aspects of life science. Like all Self-Teaching Guides, Biology helps readers build their knowledge at their own pace. Packed with useful, up-to-date information, this clear, concise volume is a valuable learning tool and reference for anyone who chooses to master the science of life. Prepare for exams with a self-test full of multiple choice questions, a review of key terms, and questions to think about at the end of each chapter. Questions and self-tests reinforce the information in each chapter and allow you to skip ahead or focus on specific areas of concern. In the second edition of Biology: A Self-Teaching Guide, you'll discover the answers to these questions and many more: * Are viruses living? * How does photosynthesis occur? * Why don't our red blood cells have nuclei? * How do tadpoles absorb their tails when they grow legs and turn into frogs? * Is cloning a form of sexual or asexual reproduction? * What is Antonie van Leeuwenhoek know for?"--
Includes bibliographical references and index
Keywords: Biologie; Biology / Study and teaching; Biology; Lehrbuch